The Influent of Colostrum Adding in Toothpaste and S Ig A Factor to Prevent School Age Caries in Ujung Tanah Sub District Makassar - Lusy Damayanti, Andi Zulkifli, Ridwan Amiruddin, Veni Hadju, Sukri Palutturi, Muh.Syafar (International Journal of Advanced Science and Technology, 2020)
Dental caries is a major public health problem. The way to prevent dental caries in children is tooth brushing with adding antimicrobial proteins in colostrum such as lactoperoxidase, lactoferrin, and lysozyme to oral health toothpaste. The purpose of this literature review is to know the influence of colostrum adding in toothpaste and Secretory IgA ( S Ig A ) to prevent school-age caries in Ujung Tanah Subdistrict, Makassar. This research used a systematic literature review. Various references were collected from online databases, including ProQuest, reports, journals, and books in the last five years. Approximately 632 of colostrum and S Ig A articles and using English in the last five years related to public health were reviewed. The role of S Ig A in improving oral mucosal defense against pathogenic bacteria Streptococcus mutants as the major etiology of dental caries. The journals were mostly from scholarly journals. The articles were screened according to the research objectives. The keywords used are colostrum and school-age caries. This study showed that Colostrum adding in oral health toothpaste in which proteins ingredients are lactoperoxidase, lactoferrin, and lysozyme and S Ig A factor is very effective in decreasing caries in children.Based on the present study revealed, we conclude that colostrum toothpaste containing lactoferrin, lactoperoxidase, and lysozyme was highly significant in reducing the salivary level of mutans streptococci in caries. Dental health education is an important thing to prevent caries. The further recommendation will be provided.